(radical din2+1)la puterea a 2=?

(radical din 3+1) la puterea2=?

(radical din 5+1) la puterea 2=?

(radical din 7+1)la puterea 2=?

(2radical din 3+1)la puterea a2=?

(2radical din 5+1) la puterea a2=?

(radical din 2+radical din 3) la puterea a2=?

(radical din 3+radical din 5)la puterea a2=?

(radical din7+radical din 2)la puterea a 2=?

(radical din 2-1) la puterea a2=?

(radical din 3 -1) la puterea a 2=?

(radical din 5-1) la puterea a2=?

(radical din 7-1) la puterea a2=?

(2 radical din 3-1) la puterea a 2=?

(2 radical din 5-1) la puterea a2=?

(radical din 2-radical din 5) la puterea a2=?

(radical din 3-radical din 3) la puterea a 2=?

(radical din 7-radical din2) la puterea a2=?

(radical din 2+1) (radical din 2-1)=?

(radical din 3+2) (radical din 3-2)=?

1

Răspunsuri

2014-02-24T18:24:17+02:00
(radical din2+1)la puterea a 2=radical din 3 la a2=radical din 9= 3
(radical din 3+1) la puterea2=radical din 4 la a 2=radical din 16=4
(radical din 5+1) la puterea 2=radical din 6 la a2=radical din 36=6
(radical din 7+1)la puterea 2=radical din 8 la a2=radical din 64=8
(2radical din 3+1)la puterea a2=16

(2radical din 5+1) la puterea a2=12
(radical din 2+radical din 3) la puterea a2=5
 (radical din 3+radical din 5)la puterea a2=8
(radical din7+radical din 2)la puterea a 2=9
 (radical din 2-1) la puterea a2=1
(radical din 3 -1) la puterea a 2=2
 (radical din 5-1) la puterea a2=4
 (radical din 7-1) la puterea a2=6
(2 radical din 3-1) la puterea a 2=4
 (2 radical din 5-1) la puterea a2=8
(radical din 2-radical din 5) la puterea a2= -3
 (radical din 3-radical din 3) la puterea a 2=0
  (radical din 7-radical din2) la puterea a2=9
 (radical din 2+1) (radical din 2-1)=1
 (radical din 3+2) (radical din 3-2)= -1